The Dirty Work of Poker: Impression Management and Identity. Issue 9 (1st September 2016) - Vines, Marcus; Linders, Annulla
ABSTRACT: Poker has penetrated mainstream popular culture in recent years with the emergence of internet poker sites and television coverage of poker's largest events. However, not only do images of seedy, back alley poker games and riverboat gamblers persist in popular culture but the language of addiction has been attached to gambling. We draw on the research on identity, stigma and "dirty work" to examine how poker players negotiate an identity on poker and how that identity is managed both within and outside of the poker community. We show how the strategies players use for deflecting stigma are continually renegotiated.